CHANGES IN PLASMA VASCULAR ENDOTHELIAL GROWTH FACTOR LEVEL AFTER INTRAVITREAL INJECTION OF BEVACIZUMAB, AFLIBERCEPT, OR RANIBIZUMAB FOR DIABETIC MACULAR EDEMA. Issue 9 (September 2018) - Hirano, Takao; Toriyama, Yuichi; Iesato, Yasuhiro; Imai, Akira; Murata, Toshinori
Abstract : Purpose: The aim of this study was to investigate the changes in plasma vascular endothelial growth factor (VEGF) level depending on the severity of diabetic retinopathy (DR) or diabetic macular edema (DME) and after intravitreal injection of bevacizumab, aflibercept, or ranibizumab for treatment of DME. Methods: Plasma VEGF level was evaluated in 72 patients with DR and changes were measured in 42 patients with DME receiving intravitreal injections of bevacizumab, aflibercept, or ranibizumab at the initial injection. Results: There were no correlations between plasma VEGF level and the severity of DME or DR. Baseline plasma VEGF level (51.9 pg/mL) was significantly reduced using bevacizumab to 11.9 pg/mL after 1 week and 24.1 pg/mL after 4 weeks ( P = 0.0130 and 0.0201, respectively). In aflibercept-treated eyes, plasma VEGF decreased from 52.2 pg/mL to 7.8 pg/mL and 12.6 pg/mL, respectively, at the same time points (both P < 0.001). No such reductions were observed in patients receiving ranibizumab. Conclusion: Baseline plasma VEGF level showed no correlations with DR or DME severity, whereas intravitreal injection of bevacizumab or aflibercept significantly reduced plasma VEGF for up to 4 weeks and ranibizumab produced no such effects. Changes in plasma VEGF level seemed not to be critical in progression or treatment of DME and DR. Abstract : Intravitreal injection of bevacizumab or aflibercept significantly reduced plasma vascular endothelial growth factor level for up to 1 month, whereas intravitreal ranibizumab produced no such effect. Plasma vascular endothelial growth factor showed no correlation with the severity of diabetic macular edema or diabetic retinopathy.